Motivation And Interpersonal Communication Of Mobile Legend Online Game Players In The MG Esport Tebet Community - Syahputra, Frank Ramadhan (Jurnal Ilmu Sosial Mamangan, 2024)
This research aims to find out the motivation and interpersonal communication of online mobile legend game players in the MG esports Tebet community. This research uses qualitative methodology. This method is often referred to as naturalistic research because it is carried out in natural conditions (as opposed to experimental conditions). Researchers used purposive sampling for the research object of this study. The participants in this research were 8 people, mainly aged between 21 and 35 years and played the online game Mobile Legends. The data acquisition method used by researchers is in-depth interviews on each research topic. This research highlights the role of McClelland's Theory in understanding motivation and interpersonal interactions in the context of the MG Esport Tebet community. This theory identifies three basic human needs, namely the need for achievement, affiliation, and power, which significantly influence individual behavior in various contexts, including in online games such as Mobile Legend. In the context of the need for achievement (Needs for achievement), Mobile Legend players in this community feel driven to achieve success and gain recognition for their achievements in the game. This motivation is reflected in their efforts to influence game strategy and act as leaders in the team. On the other hand, the need for affiliation is reflected in the warm and caring relationships between Mobile Legend players in the MG Esport Tebet community. Players enjoy being able to interact, gather, and share experiences with members of their community. In McClelland's theory, the need for affiliation refers to the interpersonal desire to be friendly and familiar with the surrounding environment, which is reflected in intimate and harmonious interactions between community members.